Conversor isolado para uso em laboratório - Garcia Neto, Salvador (2018)
This work has been a low power single phase converter with output control controlled through a digital control system and it is possible to provide a remote or alternating signal. The connection design was structured for applications where there is variation of voltage level, as in photovoltaic energy applications, where there are also voltage constants. The converter must have the voltage level included in the input and output signal during project execution and create the electrical output after the input and output signal. not for an analysis as to the feasibility of using any project of each. We present a modeling study of as well as practical results of the CC stage. Finally, we have the results of the CA stage.